1984
DOI: 10.1002/1097-4679(198401)40:1<189::aid-jclp2270400135>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Are separate black and white MMPI norms needed?: An IQ-controlled comparison of accused murderers

Abstract: Investigated racial differences in MMPI responding by comparing samples of black and white males charged with murder (N = 160). Mancova was used to control statistically for the effects of intelligence on racial differences. Prior to the use of Mancova blacks had significantly higher scores on F and MA. When the effects of intelligence were controlied F and MA were no longer significantly different for blacks and whites. However, with black and white Ss equated on IQ, significant differences emerged on the K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This fact should be kept in mind whenever one interprets a native profile. This sentiment echoes concern that has been expressed about the interpretation of profiles of blacks (Pritchard & Rosenblatt, 1980a;Holcomb et al, 1984). Third, the redundancy of Verbal Comprehension in the presence of IQ did not occur because the factor was derived from the same subscales as the WAIS full scale IQ.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This fact should be kept in mind whenever one interprets a native profile. This sentiment echoes concern that has been expressed about the interpretation of profiles of blacks (Pritchard & Rosenblatt, 1980a;Holcomb et al, 1984). Third, the redundancy of Verbal Comprehension in the presence of IQ did not occur because the factor was derived from the same subscales as the WAIS full scale IQ.…”
Section: Discussionmentioning
confidence: 78%
“…In studying race, IQ, and the MMPI, Rosenblatt and Pritchard (1978) found Gynther's (1972) black versus white differences only among groups with IQs below 93 on the Wechsler Adult Intelligence Scale (WAIS). Similarly, Holcomb and his associates found that the Gynther pattern of racial differences was eliminated when Peabody and Revised Beta IQs were used as covariates (Holcomb & Adams, 1982Holcomb, Adams, & Ponder, 1984). When education level was examined, blacks were found to score higher than whites on Pa and 5c, but only among groups with fewer than 12 years of schooling (Davis, Beck, & Ryan, 1973;Davis & Jones, 1974;Davis, 1975).…”
Section: Mmpi Minority Differences and Moderating Influencesmentioning
confidence: 93%
“…For example, Megargee and Bohn () found that men who have been incarcerated for more than 2 years showed elevations in the dimensions Pd , Sc , and Ma of the MMPI. Additionally, intelligence quotient, social status, and occupational status correlations influence the values reached in inmate population personality profiles (Holcomb & Adams, ; Holcomb, Adams, & Ponder, ; McDonald & Paitich, ). Culture and nationality are also sources of variability in the criminal personality (Boscán et al ., ; Catalá‐Miñana, Walker, Bowen, & Lila, ).…”
Section: Discussionmentioning
confidence: 99%